The Influence of BYOD Concept on Development of Learning Process in Universities - Pavlovna Sokolova, Antonina (2021)
Education is one of the largest markets promoting implementation of Bring Your Own Device BYOD. The BYOD model was originated in colleges and universities, being stimulated by technologically advanced students, who demanded it, and administrators of educational entities, who agreed that allowance to get access to the network using personal devices was a competitive advantage. Nowadays this concept attracts great attention. People depend on their personal devices and want to have the opportunity to use them anywhere in order to make their life simpler and more efficient. While BYOD implementation increases, teachers determine new methods of integration of mobile devices into learning. The use of personal mobile devices of students for learning seems to be attractive for universities, since these devices would help to reduce expenses and to support teaching and learning. The research objective: to detect the level of influence of BYOD concept on learning process. In the conclsuoins authors confirm that BYOD is the dominant model in universities.